Functional Analysis and Marker Development of TaCRT-D Gene in Common Wheat (Triticum aestivum L.) - Wang, Jiping; Li, Runzhi; Mao, Xinguo; Jing, Ruilian (Frontiers in Plant Science, 2017)
Calreticulin (CRT), an endoplasmic reticulum (ER)-localized Ca2+-binding/buffering protein, is highly conserved and extensively expressed in animal and plant cells. To understand the function of CRTs in wheat (Triticum aestivum L.), particularly their roles in stress tolerance, we cloned the full-length genomic sequence of the TaCRT-D isoform from D genome of common hexaploid wheat, and characterized its function by transgenic Arabidopsis system. TaCRT-D exhibited different expression patterns in wheat seedling under different abiotic stresses. Transgenic Arabidopsis plants overexpressing ORF of TaCRT-D displayed more tolerance to drought, cold, salt, mannitol and other abiotic stresses at both seed germination and seedling stages, compared with the wild-type controls. Furthermore, DNA polymorphism analysis and gene mapping were employed to develop the functional markers of this gene for marker-assistant selection in wheat breeding program. One SNP, S440 (T → C) was detected at the TaCRT-D locus by genotyping a wheat recombinant inbred line (RIL) population (114 lines) developed from Opata 85 × W7984. The TaCRT-D was then fine mapped between markers Xgwm645 and Xgwm664 on chromosome 3DL, corresponding to genetic distances of 3.5 cM and 4.4 cM, respectively, using the RIL population and Chinese Spring nulli-tetrasomic lines. Finally, the genome-specific and allele-specific markers were developed for the TaCRT-D gene. These findings indicate that TaCRT-D function importantly in plant stress responses, providing a gene target for genetic engineering to increase plant stress tolerance and the functional markers of TaCRT-D for marker-assistant selection in wheat breeding.